2000
DOI: 10.1074/jbc.m003661200
|View full text |Cite
|
Sign up to set email alerts
|

Protein-tyrosine Phosphatase PTPεC Inhibits Jak-STAT Signaling and Differentiation Induced by Interleukin-6 and Leukemia Inhibitory Factor in M1 Leukemia Cells

Abstract: We engineered and expressed both a wild-type and mutant cytosolic isoform of PTPε (PTPεC) in murine M1 leukemic cells, which can be induced to growth arrest and monocytic differentiation by interleukin-6 (IL-6) and leukemia inhibitory factor (LIF). Forced expression of PTPεC inhibited IL-6-and LIF-induced monocytic differentiation and apoptosis in M1 cells, whereas expression of PTPεM, a transmembrane isoform of PTPε, did not. PTPεC expression resulted in lower levels of IL-6-induced tyrosine phosphorylation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
0
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 50 publications
3
55
0
1
Order By: Relevance
“…Protein tyrosine phosphatases (PTP) including SHP-2, PTP1B and PTPeC, and CD45 dephosphorylate JAKs (Kim et al 1998;Schaper et al 1998;Tanuma et al 2000;Irie-Sasaki et al 2001;Myers et al 2001). Among them, the current study revealed that PTP1B was induced in microglia by IL-6 and LIF, but not CNTF.…”
Section: Discussionmentioning
confidence: 64%
“…Protein tyrosine phosphatases (PTP) including SHP-2, PTP1B and PTPeC, and CD45 dephosphorylate JAKs (Kim et al 1998;Schaper et al 1998;Tanuma et al 2000;Irie-Sasaki et al 2001;Myers et al 2001). Among them, the current study revealed that PTP1B was induced in microglia by IL-6 and LIF, but not CNTF.…”
Section: Discussionmentioning
confidence: 64%
“…47 Recently, the protein tyrosine phosphatase PTPaC has been implicated in the downregulation of IL-6-induced JAK1 and subsequent STAT3 tyrosine phosphorylation. 48 Whether this phosphatase is a possible candidate for the observed attenuated JAK1 phosphorylation in the AML cells upon TGF-␤1 treatment is currently under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Protein phosphatases, including CD45 and protein tyrosine phosphatase-e C (PTPeC), are also implicated in the negative regulation of Jak/STAT signaling. 186,187 Interactions Between PI3K/PTEN/Akt/mTOR, Raf/MEK/ERK and Jak/STAT pathways that regulate apoptosis Now that we have examined the basic mechanism of regulation of these pathways, we now discuss how these cascades interact to regulate apoptosis. When apoptosis is deregulated, which can occur by aberrant expression of these pathways, leukemia may arise.…”
Section: Overview Of Jak/stat Pathwaymentioning
confidence: 99%